تحليل القصيدة "لك الخيرحدّثني بظبية عامر" في ديوان الإمام الحدّاد (دراسة عروضية) - Lenti Lenti; Rosalinda Rosalinda; Mushokhikhul Khasanah (Al-Uslub: Journal of Arabic Linguistic and Literature, 2025)
The Qasida “Lakal Khairu Haddistni Bidzobyati ‘Amiri” is a qasida written by Imam Al-Haddad in his Diwan. This qasida contains zihaf, illat, and changes in the wazan. This study was conducted to determine the bahar, wazan, zihaf, and illat in the qasida “Lakal Khairu Haddistni Bidzobyati ‘Amiri”. This research is a library research, which is a type of study that refers to written sources. The researcher collected journals, books, magazines, and other documents related to the discussion. The researcher also used the analysis method formulated by Al-Khalil bin Ahmad Al-Farohidi, namely the science of ‘arudh. The researcher used Imam Al-Haddad’s Diwan as the main reference. The focus of this study is the identification of the bahar used and the changes in wazan in this qasida. The results show that this qasida uses Bahar Thowil, contains the zihaf Qobdh, and the illat Hadhf. The conclusions reached by the researcher are as follows: Zihaf Qobdh in ‘arudh occurs in 122 words, in dharb 122 words, in hashyu from shadar 109 words, in hashyu from ‘ajuz 67 words. There is only one illat, which is illat Hadhf in the 91st verse